Analisis Perilaku Pelaku Usaha Mikro dan Tindakan Masyarakat terhadap Pembuangan Limbah Industri Tahu-Tempe di Daerah Aliran Sungai Kelurahan Abian Tubuh Baru Kota Mataram - Adelia, Adelia; Khaerani, Mir’atun; Alda, Tri Rahmi Fitri; Supardiono, Supardiono; Dujana, Lalu Muhammad Aby (Biocaster : Jurnal Kajian Biologi, 2026)
The micro-scale tofu-tempeh industry in Abian Tubuh Baru Village has a strategic economic role, but its production activities produce liquid waste with a high organic load that risks degrading the aquatic ecosystem. This study aims to analyze in depth the behavior of micro-business actors in liquid waste management, as well as the community's social response to waste disposal in the Abian Tubuh Baru Village Watershed. The research method used is descriptive qualitative with a case study approach. Data were collected through field observations and in-depth interviews with business actors and the surrounding community who were selected purposively until data saturation was achieved. Data analysis was carried out thematically using the Miles & Huberman interactive model. The results showed that liquid waste is still discharged directly into water bodies without treatment due to the persistence of habitual factors, limited environmental literacy, and the absence of waste processing infrastructure facilities. This condition causes a significant decline in river water quality, characterized by changes in physical parameters (color and turbidity), and the emergence of a pungent odor due to organic decomposition. The community shows a tendency to act passively through environmental normalization by choosing to stop using river water rather than carrying out social control. These findings imply the urgency of community-based environmental awareness-building interventions for sustainable river pollution mitigation.